Manajemen Komunikasi dalam Event Musik Underground di Demajors Records Tangerang - Wahyu Rama Nugraha; Luna Safitri Salsabil; Aulian Khairani (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
An event is an activity that has a specific purpose and is held to meet the needs of the community. In the modern era like today, event activities have become a rapidly growing phenomenon and are increasingly in demand by many people. Events can be formal activities such as seminars, conferences, or business meetings, as well as non-formal activities such as music concerts, festivals, exhibitions, and so on. This research aims to find out how event management, supporting factors and inhibiting factors in holding Underground music events at Demajors Records Tangerang. The method used is Qualitative research method. The theory used is Communication Management Theory. The paradigm used is constructivism. Data collection techniques were carried out by in-depth interviews, observation and documentation. The results showed that Demajors Records Tangerang has used 4 stages of POAC (Planning, Organizing, Actuating, Controlling) indicators proposed by Parag Diwan.